2020
DOI: 10.4149/gpb_2019057
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 promotes the secretion of pro-inflammatory cytokines by macrophages to aggravate H/R-induced cardiomyocyte injury via activating NF-κB signalling

Abstract: The upregulation of proprotein convertase subtilisin/kexin type 9 (PCSK9) was reported to be involved in regulating the levels of inflammatory markers and apoptosis in macrophages. This study aims to investigate the function and regulation of PCSK9 in myocardial ischaemia. The results of our study showed dramatically increased expression of PCSK9 induced by hypoxia/reoxygenation (H/R) stress rather than by apoptosis in primary murine cardiomyocytes and HL-1 cells. Moreover, PCSK9 promoted H/R-induced pro-infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 27 publications
0
33
0
1
Order By: Relevance
“…PCSK9 was found to induce an inflammatory response on macrophages by releasing pro‐inflammatory cytokines, such as tumor necrosis factor (TNF)‐α, interleukin (IL)‐1 and IL‐6 [35]. This has also been confirmed in hypoxia/reoxygenation (H/R) stress, where primary murine cardiomyocytes released TNF‐α, IL‐6 and IL‐1β and enhanced the production for these pro‐inflammatory cytokines by macrophages undergoing H/R [36]. Therefore, the positive relationship between PTX3 and PCSK9 should not be surprising and is similar to what reported by Rannikko et al, who observed a significant positive correlation between PCSK9 and CRP levels [17].…”
Section: Discussionmentioning
confidence: 99%
“…PCSK9 was found to induce an inflammatory response on macrophages by releasing pro‐inflammatory cytokines, such as tumor necrosis factor (TNF)‐α, interleukin (IL)‐1 and IL‐6 [35]. This has also been confirmed in hypoxia/reoxygenation (H/R) stress, where primary murine cardiomyocytes released TNF‐α, IL‐6 and IL‐1β and enhanced the production for these pro‐inflammatory cytokines by macrophages undergoing H/R [36]. Therefore, the positive relationship between PTX3 and PCSK9 should not be surprising and is similar to what reported by Rannikko et al, who observed a significant positive correlation between PCSK9 and CRP levels [17].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, whereas CD36 decline might be beneficial in the short-term post-ischaemia because of improved myocardial efficiency rates, levels of CD36 need to be restored upon glucose and intracellular TG storage depletion in order to meet cardiac energy demands (Kim and Dyck, 2016). In this regard, taking into consideration that PCSK9, which is found to be enhanced by hypoxia/reoxygenation (Yang et al, 2020), has also shown to degrade CD36 beyond the LDL-R (Demers et al, 2015), PCSK9 inhibition might hold promise as a therapeutic strategy to modulate myocardial CD36 content and expression and consequently FA metabolism levels in the setting of MI.…”
Section: Fatty Acid Translocase Cd36 and Pcsk9 In Irimentioning
confidence: 99%
“…The up-regulation of PCSK9 is driven by sterol response element binding protein 2 (SREBP-2) and hepatocyte nuclear factor 1 α (HNF1α), both of which are the predominate transcription factors for PCSK9 (Zhang et al, 2014). PCSK9 is also expressed in the myocardium and is significantly up-regulated in hypoxia/reoxygenation-stimulated primary murine cardiomyocytes compared with cells grown in normoxic environments (Ding et al, 2018;Yang et al, 2020). Again, in MI the maximum expression of PCSK9 was found in the border zone 1 week after left coronary artery (LCA) ligation (Ding et al, 2018).…”
Section: Effects Of Pcsk9 Beyond Ldl Reduction: Impact On Irimentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent experimental data suggest that PCSK-9 could be involved in the release of pro-inflammatory cytokines by macrophages after hypoxia and reperfusion injury. The authors even suggest that PCSK-9 could alleviate the activation of the nuclear factor "kappa-light-chain-enhancer" of activated B-cells (NFKB) pathway after experimental myocardial ischemia [20]. Furthermore, PCSK-9 also interacts with the oxidized-LDL-receptor (LOX-1), which is a central regulator of inflammation, atherogenesis and apoptosis of endothelial cells.…”
Section: Introductionmentioning
confidence: 99%